HUBUNGAN KUALITAS HIDUP KELUARGA DENGAN STATUS GIZI PADA BALITA DI KECAMATAN PANTI KABUPATEN JEMBER - Husniyeh, Maviratul; Susanto, Tantut; Susumaningrum, Latifa (Poltekkes Kemenkes Kupang, 2023)
Families have an important role in fulfilling enough nutrition in children. Hence, family quality life greatly affects in fulfilling nutritional status. The aimed of this study was to analyze the relationship of family quality of life and nutritional status among under five children. A cross-sectional study was conducted among 248 family using consecutive sampling. A self-administered questionnaire was used to measure sociodemographic of family and their children, while the Family Quality of Life Questionnaire was used to analyze the quality of family life and Anthropometric calculations based on BB/U, TB/U and BB/TB with the interpretation of z-score used to analyze nutritional status among under five children. The relationship between the quality of family life and the nutritional status among under five children was analyzed by Kruskal Wallis. This study showed children with nutrition based on BB/U 303 children, based on TB/U 226 children, and based on BB/TB 344 children. There were a significantly relationship between FQOL and nutritional status of children (p-value < 0,05). The study concludeed, FQOL relationship with the nutritional status of children. Therefore, the improve the quality of family life in order to improve the nutritional status of children who are more normal to prevent disruption in the growth and development of children.